Chemosensing of nitroaromatics with a new segmented conjugated quaterphenylene polymer - del Rosso, Pablo Gabriel (2011)
A new approach for introducing porosity in fluorescent polymer films to increase sensing performance is presented. A novel segmented conjugated polymer composed of p-quaterphenylene segments tethered by their meta positions along the polymer main chain by 2,2-isopropylene spacers was synthesized. The bent nature of its microstructure generates amorphous morphologies that let analytes diffuse rapidly within the films. Fluorescence quenching studies with polymer films and methanol solutions of nitroaromatics showed high sensitivity, fast response and reversibility of the fluorescence quenching. Thus, half of the maximum quench (Q 50%) occurred with nitrobenzene at the micromolar range in less than 1 min in a reversible manner. © 2011 Elsevier Ltd. All rights reserved.